Effect of uniformity and surface morphology of Pt nanoparticles to enhance oxygen reduction reaction in polymer electrolyte membrane fuel cells. (8th August 2022) - Lim, Su-yeong; Kim, Sun-I; Lee, Min Seong; Bak, Su-Jeong; Lee, Duck Hyun; Kwon, Se-Hun; Kim, Taehyo
Abstract: Platinum (Pt)-based electrocatalysts supported by reduced graphene oxide (rGO) is fabricated under microwave-assisted polyol method with various nucleation and growth conditions. The surface morphologies of the Pt nanoparticles (NPs) under various reaction conditions owing to different Pt NP sizes and inter-particle spacings are investigated by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, thermogravimetric analysis, cyclic and linear sweep voltammetry, and electrochemical impedance spectroscopy. The synthesized Pt/rGO catalyst under nucleation and growth times of 10 s and 50 s, respectively, exhibits excellent catalytic activity with increased electrochemical surface area, high density, good uniformity and surface morphology with a particle size and inter-particle spacing of 2.16 nm and 17.2 nm, respectively. These results elucidate the relationship between the Pt NP morphology distribution and oxygen reduction reaction of catalysts in polymer electrolyte membrane fuel cell systems. We also highlight the important role of size and inter-particle spacing on the Pt electrochemical catalystic performance. Highlights: The Pt/rGO catalyst was synthesized by microwave-assisted polyol method with various nucleation and growth condition. The morphology distribution and particle size of Pt NPs exhibited key factor for ORR improvement of catalysts. The Pt/rGO catalyst shows improvement of electrochemical performance with a favorable surface morphology of Pt NPs.